LABOUR MARKETS FOR RURAL POPULATION: COMMUTING AND MIGRATION ABROAD - Chmieliński, Paweł (Economics of Agriculture, 2013)
In the absence of a satisfactory level of jobs offered in rural areas, achieving of the supply demand balance in the labour market can supported by labour migration, both internal and external. Paper discusses the labour market for rural population in terms of commuting and working abroad. Study showed that that the average labour market for the rural inhabitants is local and consists of cities located close to the place of residence. They generate demand for labour force and allow rural development through the transfer of knowledge and capital. Moreover, in 88.2% of surveyed villages the migrations abroad were reported. Next to Germany, UK and Ireland, an important direction of migration of the rural population were the Netherlands and Belgium, Italy and the Scandinavian countries.